2020
DOI: 10.1029/2019wr026715
|View full text |Cite
|
Sign up to set email alerts
|

Subcore Scale Fluid Flow Behavior in a Sandstone With Cataclastic Deformation Bands

Abstract: Accurate determination of petrophysical and multiphase flow properties in sandstones is necessary for reservoir characterization, for instance for carbon dioxide and hydrogen storage in geological formations or for enhanced oil recovery. Several studies have examined the effect of heterogeneities, such as fractures, bedding planes, and laminae, on core-scale fluid flow. However, the influence of deformation bands that commonly occur in high porosity sandstones is poorly understood. In this study, we consider a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…The mechanisms discussed above explain how and why cement precipitation would occur within the band and in its proximity, as observed on-site. Our field observations confirm the theoretical and flow simulations as well as the analog experiments, which demonstrated that DBs can negatively affect the fluid flow in porous sandstones (e.g., Rotevatn and Fossen, 2011;Antonellini et al, 2014;Romano et al, 2020) and enhance cement precipitation (e.g., Lander et al, 2009;Williams et al, 2015).…”
Section: Role Of Deformation Bands In Fluid Flow and Diagenesissupporting
confidence: 86%
See 2 more Smart Citations
“…The mechanisms discussed above explain how and why cement precipitation would occur within the band and in its proximity, as observed on-site. Our field observations confirm the theoretical and flow simulations as well as the analog experiments, which demonstrated that DBs can negatively affect the fluid flow in porous sandstones (e.g., Rotevatn and Fossen, 2011;Antonellini et al, 2014;Romano et al, 2020) and enhance cement precipitation (e.g., Lander et al, 2009;Williams et al, 2015).…”
Section: Role Of Deformation Bands In Fluid Flow and Diagenesissupporting
confidence: 86%
“…The petrophysical properties (porosity, permeability, capillary entry pressure) of DBs influence fluid flow and localize diagenesis and cement precipitation. Cataclastic DBs increase flow tortuosity in reservoirs and produce capillary barriers that severely baffle the flow at the reservoir scale and limit cross-flow between host rock compartments (Harper and Mofta, 1985;Edwards et al, 1993;Lewis and Couples, 1993;Leveille et al, 1997;Gibson, 1998;Antonellini et al, 1999Antonellini et al, , 2014Sternlof et al, 2004;Rotevatn and Fossen, 2011;Ballas et al, 2012;Medici et al, 2019;Romano et al, 2020). Smaller pores within bands result in higher capillary forces than in the host rock.…”
Section: Role Of Deformation Bands In Fluid Flow and Diagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In situ characterization studies of sub-core scale multiphase fluid properties in heterogeneous rocks to date have typically focused on simple structures, such as fractures, bedding planes, laminae (Alemu et al, 2013;Hingerl et al, 2016;Krevor et al, 2011;Li et al, 2020;Ni et al, 2019;Shi et al, 2011) and individual deformation bands (Romano et al, 2020). However, a combination of geologic structures is often present in the subsurface, leading to more extreme heterogeneities with complex geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In all cataclastic bands, fine crushed grains fill available pore spaces, decreasing porosity and permeability of the host rock by several orders of magnitude (Aydin and Johnson, 1978;Antonellini and Aydin, 1994;Ballas et al, 2015;Deng et al, 2015;Fossen et al, 2007;Taylor and Polland, 2000). Cataclastic deformation bands are usually characterized by higher capillary entry pressure values when compared to the surrounding rock (Romano et al, 2020;Torabi et al, 2013;data from Fisher et al, 2005, summarised in van Ojik et al, 2020). A single deformation band is only able to accommodate few millimeters, or rarely a few centimeters of displacement (Aydin and Johnson, 1978).…”
Section: Introductionmentioning
confidence: 99%